2016
DOI: 10.3329/bjsr.v29i1.29753
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contents in soils affected by industrial activities in a southern district of Bangladesh

Abstract: A research was done to focus on the level of heavy metal pollution by three point sources in Barisal, a southern district of Bangladesh. Soils were collected from four distinct distances (100 m, 200 m, 400 m and 600 m from the point of discharge) of three different industrial sites, namely textile, cement and medicine industry. Maximum build-up of heavy metals was found in the vicinity of textile industry, while the minimum was observed in soils of medicine industry. Cu, Cr, Cd, Mn and Ni were found in the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Similarly, heavy metals have been spread from industrial activities to suburban soils and nearby farmlands in large industrial cities in Bangladesh (Zakir et al 2015;Begum and Huq 2016). Tanneries with lack of environmental treatment discharge a large amount of heavy metals through their effluents.…”
Section: Trophic Transfer Of Heavy Metals Through Food Webs In Bangladeshmentioning
confidence: 99%
“…Similarly, heavy metals have been spread from industrial activities to suburban soils and nearby farmlands in large industrial cities in Bangladesh (Zakir et al 2015;Begum and Huq 2016). Tanneries with lack of environmental treatment discharge a large amount of heavy metals through their effluents.…”
Section: Trophic Transfer Of Heavy Metals Through Food Webs In Bangladeshmentioning
confidence: 99%
“…Waste water from the Hazaribagh leather industrial area in Dhaka was found to be responsible for high Cr (976 ± 153 mg/kg) concentrations in the local soil [27]. Soils from several industrial areas in Gazipur and Barisal also presented much higher Cd than the recommended values [29,32].…”
Section: Soil Heavy Metal and Metalloid Pollutionmentioning
confidence: 99%
“…47 In Chittagong, the New Market and Director's office areas are two of the city's busiest areas, and road dust and vehicle exhaust were the primary sources of Pb pollution in Chittagong. 78 Near a battery manufacturing plant in Munsiganj Sadar Upazila, including the surrounding residential areas, the concentration was higher than other locations.…”
Section: Discussionmentioning
confidence: 94%